Mengurangi Perilaku Mengigit Jari Tangan terhadap Anak Tunagrahita Sedang melalui Teknik Aversi - Ani, Fitri; Efendi, Jon (Jurnal Penelitian Pendidikan Khusus, 2024)
This research aims to reduce the finger biting behavior of intellectual disability children that found at SLB N1 Sawahlunto. There is a student who experienced problems with excessive behavior (biting his fingers). In learning activities, the kids often displayed this habit so that learning in the class was disrupted and caused the fingers of the child's hands become defective and unattractive to look at. To overcome this problem, the researcher used "Aversion Techniques" to reduce finger biting behavior. The research method used in this study was Single Subject Research (SSR) with an A-B-A design. The research variable was reduce finger biting behavior of intellectual disability children. Data collection techniques include observation, documentation, data collection format and using graphic visual analysis. The results of the study showed that the finger biting behavior of intellectual disability children was reduced after the Aversion technique was applied to the subjects. This condition was proved based on data collection after the intervention was given.